Development of methylcellulose‐based sustained‐release dosage by semisolid extrusion additive manufacturing in drug delivery system. Issue 2 (9th August 2020) - Cheng, Yiliang; Qin, Hantang; Acevedo, Nuria C; Shi, Xiaolei
Abstract: The objective of this study is to fabricate customized dosage forms using extrusion‐based 3D printing for the sustained delivery of theophylline. The therapeutic paste was prepared by combining various doses of theophylline (0, 75, 100, and 125 mg) with different concentrations of methylcellulose (MC) A4M (8, 10, and 12%). The paste was then 3D printed into semisolid tablets under optimized printing conditions. The rheological properties of printing pastes were related to the 3D printability. Our results indicated that to be 3D printed using the current platform, the storage modulus (G′) of the printing paste should be higher than the loss modulus (G″) during the frequency sweep (0.1–600 rad/s), and the tan δ should fall in the range of 0.25–0.27 at 0.63 rad/s. The printed tablets formulated with 10% MC showed the highest overall quality, considering the aspects of resolution, texture, and shape retention regardless of the dosage. The scanning electron microscopy images indicated that the cross‐linked structure of MC A4M formed the microscale porous microstructure, which has the potential to embed the theophylline, thus delayed the release through the barrier effect. The in vitro dissolution test revealed that the 3D printed tablets exhibited a sustained release during the first 12 hr. The findings in this study will support the development of customized, personalized medicine with improved efficacy.